Etika Bisnis terhadap Loyalitas Pelanggan melalui Kepuasan Pelanggan sebagai Mediasi di Pasar Ruang Kantor Jakarta - Adhianto, Cahyo; Wahyono, Budi; Latif, Rovi (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2025)
Jakarta's office sector faces oversupply challenges and fierce market competition, compelling organizations to pursue differentiation strategies via ethical business practices. This research investigates how business ethics influences customer loyalty through customer satisfaction as a mediating factor within Jakarta's office market environment. The study utilized a quantitative methodology via survey technique involving 100 office space users selected based on minimum service usage criteria of once. Linear regression analysis and Sobel Test were employed for data examination to assess mediation impacts. Findings revealed that business ethics positively and significantly influences customer satisfaction (? = 0.889, p < 0.001) and customer loyalty (? = 0.771, p < 0.001). Customer satisfaction demonstrated positive and significant impact on customer loyalty (? = 0.820, p < 0.001). Mediation analysis verified customer satisfaction's role in connecting business ethics with customer loyalty (z = 6.047, p < 0.001). Business ethics serves as a crucial element in fostering customer loyalty through both direct pathways and enhanced customer satisfaction. These results offer strategic guidance for office facility managers to emphasize ethical business value implementation as a competitive strategy in addressing market challenges.